Drivers of Insect Diversity and Community Turnover in Protected Tropical Deciduous Forests of Mexico - Pilar Benites; Antonio García‐Bautista; Natalia Bautista‐Briseño; Flavio E. Zárate‐Hernández; Ek del‐Val; Antonio Hernández‐López; Enrique Ramírez‐García; Diana P. Zavala‐de la Rosa; Alfried P. Vogler; Alejandro Zaldívar‐Riverón (Environmental DNA, 2025)
ABSTRACT Tropical deciduous forests (TDFs) are among the world's most biodiverse yet endangered ecosystems. In the Neotropics, TDFs have experienced substantial range reductions due to land use changes, with profound implications for their insect diversity, much of which remains unknown. Here we conducted extensive Malaise trap sampling and metabarcoding of whole insect communities to investigate the influence of seasonality, anthropogenic disturbance, and habitat physical parameters on insect taxonomic diversity and community structure in two protected TDFs on the Pacific coast of Mexico, at Chamela (Jalisco) and Huatulco (Oaxaca), located approximately 1000 km apart. We recorded high insect species diversity, with 4626 and 3672 MOTUs identified at Chamela and Huatulco, respectively, of which only 18.5% were shared between the two regions. Nonmetric multidimensional scaling (NMDS), fourth‐corner model, and zeta diversity analyses revealed a complex, multi‐factorial community turnover driven by seasonal fluctuations and varying disturbance levels. Species turnover also was partially explained by the distance between sites and specific forest features (total deadwood volume, tree diversity, canopy coverage), suggesting that habitat heterogeneity shapes local insect diversity and community turnover. Our findings highlight the unexpectedly high local and regional turnover in insect communities in Neotropical TDFs, underscoring the importance of conservation of each remaining forest reserve and their semi‐disturbed surroundings.